Variation in antiretroviral treatment coverage and virological suppression among three HIV key populations - Laut, Kamilla Grønborg; Shepherd, Leah; Gottfredsson, Magnus; Sedlacek, Dalibor; Knysz, Brygida; Begovac, Josip; Radoi, Roxana; Schmied, Brigitte; Chkhartishvili, Nikoloz; Florence, Eric; Ristola, Matti; Fätkenheuer, Gerd; et al. (AIDS (London, England), 2018)
OBJECTIVES: We assessed differences in antiretroviral treatment (ART) coverage and virological suppression across three HIV key populations, as defined by self-reported HIV transmission category: sex between men, injection drug use (IDU) and heterosexual transmission. DESIGN: A multinational cohort study. METHODS: Within the EuroSIDA study, we assessed region-specific percentages of ART-coverage among those in care and virological suppression (<500 copies/ml) among those on ART, and analysed differences between transmission categories using logistic regression. RESULTS: Among 12 872 participants followed from 1 July 2014 to 30 June 2016, the percentages of ART-coverage and virological suppression varied between transmission categories, depending on geographical region (global P for interaction: P = 0.0148 for ART-coverage, P = 0.0006 for virological suppression). In Western [adjusted odds ratio (aOR) 1.41 (95% confidence interval 1.14-1.75)] and Northern Europe [aOR 1.68 (95% confidence interval 1.25-2.26)], heterosexuals were more likely to receive ART than MSM, while in Eastern Europe, there was some evidence that infection through IDU [aOR 0.60 (95% confidence interval 0.31-1.14)] or heterosexual contact [aOR 0.58 (95% confidence interval 0.30-1.10)] was associated with lower odds of receiving ART. In terms of virological suppression, people infected through IDU or heterosexual contact in East Central and Eastern Europe were around half as likely as MSM to have a suppressed viral load on ART, while we observed no differences in virological suppression across transmission categories in Western and Northern Europe. CONCLUSION: In our cohort, patterns of ART-coverage and virological suppression among key populations varied by geographical region, emphasizing the importance of tailoring HIV programmes to the local epidemic.
Keywords: Drug Utilization; Viral Load; sexuální chování; vysoce aktivní antiretrovirová terapie; Europe; Cohort Studies; výsledek terapie; Evropa; Middle Aged; mužské pohlaví; Antiretroviral Therapy, Highly Active; HIV infekce; Anti-Retroviral Agents; Adult; kohortové studie; setrvalá virologická odpověď; Sustained Virologic Response; Sexual Behavior; ženské pohlaví; Humans; zeměpis; Population Groups; populační skupiny; antiretrovirové látky; lidé středního věku; virová nálož; spotřeba léčiv; dospělí; Geography; Female; HIV Infections; Treatment Outcome; lidé; Male